MODELLING OF ACCESS TO MOSQUITO TREATED NET IN NIGERIA: USING MULTILEVEL LOGISTIC REGRESSION APPROACH - Iornem, Tersoo Valentine; Abdulkardir, Sauta Saidu; Akinrefon, Adesupo A.; Ornguga, Ianngi Gabriel (FUDMA JOURNAL OF SCIENCES, 2023)
This research examined the current status of access to Mosquito Treated Net (MTN) for children under five years in Nigeria. Despite the National malaria elimination programme recommendation of long-lasting insecticide treated net as the cornerstone of malaria prevention in Nigeria, there exist disparity in access to this MTN. The data for the study was extracted from the 2018 National Demographic Health Survey (NDHS). Descriptive statistic was adopted to describe and explain the effects of the variances present in the study on the variables of interest using STATA15 software are presented. The results reveal that out of the 8627 household with under five children considered in the analysis 7431 (86.14%) have access to MTN while 1196 (13.86%) have no access to MTN at the time of data collection. The wealth index of parents, educational attainment and regions were found to be the major determinants of under-5 access to MTN in Nigeria. The results also reveals that the null random intercept model best fit the data. The intra- class-correlation coefficient reveals a regional variation in the numbers of under-5 that have access to MTN across geopolitical zones in Nigeria. The result shows a statistically significant result for the random intercepts at 5% level of significance with a variation of 0.044154. The estimate of the intra-class-correlation coefficient indicates a total variability of 0.2051(20.51%). The research concludes that wealth index, educational attainment and region are the major determinants of access to MTN in Nigeria.